Lombok as An Indonesian Halal Travel Destination - Helmi Haris; Muh. Nashirudin (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study examines Lombok, as an Indonesian halal travel destination, through Global Muslim Travel Index (GMTI) analysis. GMTI requires four main indicators of assessing a halal destination, namely access, communication, environment and service. This study finds that Lombok is a promising island to be a halal travel destination, even it will be the best halal tourism place in Indonesia. However, the development of this destination should put in priority. The local government should take part in translating the halal destination concept to the grassroot level of tourism industry, whether in terms of tradition, culture, environment and other main indicators. Keywords: Lombok, halal tourism, travel destination, GMTI